Expert System dan Aplikasinya dalam Auditing: Suatu Metode Mempelajari Pertimbangan Materialitas - Erni Suryandari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2001)
Expert system is an intellegence computer system that uses knowledge and inference procedures to solve quite a difficult problem which in unstructured in its nature. This purpose of this study is to discuss the benefit of expert system as an aid in decision making by auditors in auditing financial statement, especially when auditors are making audit planner. In making audit planner, expert system helps evaluate audit risk and judgment materiality. Judgment materiality planning will effect the nature, time and the extent of audit procedure. In the future, expert system will be a challenge to the accounting profession in order to get the benefit from the coming technology to improve performance and reduce cost.